Microvirga indica sp. Nov., an arsenite-oxidizing alphaproteobacterium, isolated from metal industry waste soil - Tapase, S. R. (International Journal of Systematic and Evolutionary Microbiology, 2017)
A novel Gram-stain-negative bacterium, strain S-MI1bT, belonging to the genus Microvirga was isolated from a metal industry waste soil sample in Pirangut village, Pune District, Maharashtra, India. Cells were non-spore-forming, small rod-shapes, motile and strictly aerobic with light-pink colonies. The strain grew in 0-7.0 % (w/v) NaCl and at 25-45 °C, with optimal growth at 40 °C. The predominant fatty acids detected were summed feature 8 (C18 : 1 ω7c and/or C18 : 1 ω6c) and C19 : 0 cyclo ω8c. The predominant isoprenoid quinone was Q-10. The G+C content was 67.2 mol% and DNA-DNA relatedness values between strain S-MI1bTand Microvirga subterranea DSM 14364T and Microvirgaaerophila 5420S-12T were 53.9 and 54.8 %, respectively. Phylogenetic analysis, based on 16S rRNA gene sequences, indicated that strain S-MI1bT is a member of the genus Microvirga, with greatest sequence similarities of 97.7 and 97.4 % with M. subterranea DSM 14364T and M.aerophila 5420S-12T, respectively. Phylogenetic analysis showed that strain S-MI1bT forms a clade with the type strain of M. subterranea DSM 14364T, and was readily distinguishable from it due to various phenotypic characteristics. The combination of genotypic and phenotypic data suggests that the isolate represents a novel species of the genus Microvirga, for which the name Microvirga indica sp. nov. is proposed. The type strain is S-MI1bT (=NCIM-5595T=KACC 18792T=BCRC 80972T)